Does an alternate-day modified fasting diet improve premenstrual syndrome symptoms and health-related quality of life in obese or overweight women with premenstrual syndrome? A randomized, controlled trial - Hooshiar, Saeedeh Hosseini; Yazdani, Akram; Jafarnejad, Sadegh (Frontiers in Nutrition, 2024)
Premenstrual syndrome disorder (PMS) is a condition that affects health-related quality of life (HRQoL) and encompasses a variety of symptoms, including psychological, physical, and behavioral symptoms. Some evidence suggests that an increase in body mass index (BMI) can reduce both HRQoL and menstrual quality. This is because body fat tissue can affect menstrual cycles by changing the estrogen/progesterone ratio. This study investigated the impact of two diets alternate-day modified fasting (ADMF) and daily calorie restriction (DCR) -on PMS syndrome and HRQoL. The study was a randomized controlled, open-label trial that lasted for eight weeks and involved 60 obese/overweight women. Participants were recruited from the Health Service Centers of Kashan University of Medical Sciences using simple random sampling. The study compared the impact of the ADMF and DCR diets on HRQoL and PMS symptoms. Patients were classified based on their BMI and age, and then allocated to either the intervention (ADMF) or control (DCR) group using a random numbers table. The study measured HRQoL, PMS severity, weight, BMI, body fat mass, waist circumference, fat-free mass, and skeletal muscle mass before and after the study. The study had an almost 18% dropout rate. Significant improvements were observed in mood lability (P=0.044) and expressed anger (P<0.001) concerning PMS symptoms. However, no significant differences were detected in the changes of other COPE subscales. The ADMF diet had a significant impact on the 12-item Short-Form Health Survey (SF-12) total score (P<0.001) and physical function subscales (P=0.006) as well as mental health (P<0.001) when compared to the control diet. This implies that the ADMF diet increased both the SF-12 total score and its subscales. The intervention led to improvements in HRQoL, physical function, and mental health. Additionally, significant improvements in BMI and weight were observed between the two groups pre-and post-study (P<0.001). Anthropometric data, including body fat mass and waist circumference, showed significant improvement (P<0.001 and P=0.029, respectively) before and after the study. However, there were no significant changes in fat-free mass (P=0.936) and skeletal muscle mass (P=0.841) between the two groups. the study suggested that ADMF can improve HRQoL, mood lability, and expressed anger.